Influência da reanatomização e do aparelho fotopolimerizador na resistência de união de pinos de fibra de vidro - Estudo in vitro - Schoenhals, Gustavo do Prado (2021)
Teeth with extensive loss of structure may compromise the retention of restorations to the dental remnant, and the use of pins is recommended. In vitro study the union of fiberglass pins to the root dentin due to different modes of resuscitation, photopolymerizers and root regionalization. Ninety (n = 10) uniradicular bovine roots were used in a 3 x 3 x 3 factorial study with subdivided plots: Customization of the pin, varying the presence and type of resin (Without resuscitation, Conventional Resin and Bulk Fill Resin); Light curing (Valo, Radii-cal, Rainbow); and Root third (cervical, middle and apical). Each sample resulted in 9 specimens (3 slices from each root third), which were submitted to the push out test and the failure mode was evaluated. Three-way ANOVA did not show differences for a triple interaction (p = 0.984) or for doubles (p = 0.264; p = 0.993 and p = 0.779), but for the three factors individually (p <0.001). The Tukey test (5%) showed for the Reanatomization Factor the Bulk Fill (8.16MPa) and Z350 (7.40MPa) groups superiority to the Control group (4.92MPa), without differing from each other. All photopolymerizers differed, with Valo superiority (9.36MPa), Radii (6.96MPa) intermediate, and Raiwbow inferiority (4.17MPa). The cervical root third (7.81MPa) was superior and the lower apical one (5.80MPa), with the middle third (6.88MPa) intermediate and without differing from the others. It is concluded that the resuscitation of fiberglass pins increases the bond strength to the root dentin, regardless of the resin used, with damage in the apical third and when photopolymerizers with lower light intensity are used.